Moderate Hypothermia Effectively Alleviates Acetaminophen-Induced Liver Injury With Prolonged Action Beyond Cooling - Tan, Yeong Lan (Dose Response, 2020)
Acetaminophen (APAP) overdose accounts for the highest incidence of acute liver failure, despite the availability of an antidote i.e. N-acetylcysteine. This calls for alternative strategies to manage APAP-induced liver injury (AILI). Therapeutic hypothermia has been explored in past studies for hepatoprotection, but these phenomenal reports lack clarification of its optimal window for application, and mechanistic effects in specific AILI. Hence, we conducted an in vitro study with transforming growth factor-α transgenic mouse hepatocytes cell line, TAMH, and human liver hepatocytes cell line, L-02, where cells were conditioned with deep (25°C) or moderate (32°C) hypothermia before, during or after APAP toxicity. Cell viability was evaluated as a hallmark of cytoprotection, along with cell death. Simultaneously, cold shock proteins (CSPs) and heat shock proteins expressions were monitored; key liver functions including drug-metabolizing ability and hepatic clearance were also investigated. Herein, we demonstrated significant hepatoprotection with 24-hour moderate hypothermic conditioning during AILI and this effect sustained for at least 24 hours of rewarming. Such liver preservation was associated with a CSP—RNA-binding motif protein 3 (RBM3) as its knockdown promptly abolished the cytoprotective effects of hypothermia. With mild and reversible liver perturbations, hypothermic therapy appears promising and its RBM3 involvement deserves future exploration.